Mechanical and crystallisation properties of polyetheretherketone polymer from dry solid lubricants - Ladipo, Taiwo Lolade (Vaal University of Technology, 2023)
Polyetheretherketone (PEEK) polymer suffers high viscosity during fused filament fabrication (FFF). Adding solid lubricants as fillers to PEEK should reduce its viscosity. However, very little research has been conducted on the tribological properties of PEEK printed using FFF. This study dealt with filament-making, tensile properties, crystallinity, and tribological characterisation of FFF-printed PEEK impregnated with dry solid lubricants. PEEK, graphite, and Molybdenum disulphide (MoS2) were sourced, tested, and analysed. Three active functional groups were found in the PEEK: oxy, phenyl, and carbonyl. While the MoS and graphite powder indicated sulfide and Carbon functional groups. The PEEK and both lubricants had an average particle diameter of 100 microns. Three weight ratios of each solid lubricant were mechanically blended into PEEK powder. Seven samples were prepared using a tabletop extruder. Each filament was 3D printed into 35 dog bones and seven discs for ultimate tensile testing, X-ray diffraction analysis (XRD), and disc on-pin testing. The diagrammatic Hermans-Weidinger approach with XRD analysis was used to evaluate the degree of crystallinity. It was established that the MoS2-filled PEEK is better than the graphite-filled PEEK. MoS2-filled PEEK reinforces as the weight content of MoS2 increases up to 104 MPa at 10 wt%. This reinforcement suggests perfect adhesion between PEEK and MoS2. On the other hand, the graphite-filled PEEK decreased in tensile strength to 36 MPa due to agglomeration at 10 wt% filling of graphite. No existing planar peaks were destroyed by introducing MoS2 and graphite, but a new peak was formed per solid lubricants and intensified on the increase of the solid lubricants. Generally, the MoS2-filled PEEK has the best-recorded crystallinity level at about 70% for 5 wt.% while the lowest recorded value was 3 wt.% of graphite valued at 31%. The tribological observation showed that the average response time for pure 3D-printed PEEK is about 950 seconds, indicating that FFF-printed PEEK has a weak capacity to minimise friction independently. Impregnating PEEK with MoS2 and Graphite decreases the response time by about 73%. However, the coefficient of friction of graphite-filled PEEK was initially reduced but started increasing after 5 wt.% due to agglomeration. The MoS2-filled PEEK has a minimum of 30 % decrease in the wear rate, while the graphite-filled PEEK initially decreases to 9% but later spikes to about 6% due to agglomeration. The agglomeration of Graphite in PEEK at a high weight fraction makes graphite a non-perfect choice for FFF compared to MoS2.
M. Eng. (Department of Industrial Engineering, Operation Management, and Mechanical Engineering: Mechanical Engineering, Faculty of Engineering and Technology), Vaal University of Technology.
Keywords: Polyetheretherketone polymer; Dry solid lubricants; Filament-making; Tensile properties; Crystallinity; Tribological characterisation; Fused filament fabrication; Dissertations, Academic -- South Africa.; Mechanical engineering.; Polymeric composites.; Polymers.; Solid lubricants.